Urinary exosomal miRNA-451a can be used as a potential noninvasive biomarker for diagnosis, reflecting tubulointerstitial damage and therapeutic response in IgA nephropathy - Qiong Zhang; Yan Zhao; Yankun Luo; Songjia Guo; Haizhu Hou; Xiaoli Han; Yun Zhou (Renal Failure)
To investigate the potential clinical value of urinary exosomal (uE) miR-451a as a biomarker for IgAN, urinary exosomes were isolated from 40 patients with IgAN, 30 patients with primary renal diseases without IgA as disease controls (non-IgAN group) and 21 healthy controls (HCs). The expression of miR-451a within exosomes was examined by reverse transcription-quantitative polymerase chain reaction (RT-qPCR). uE miR-451a was significantly upregulated in patients with IgAN compared to non-IgAN and HCs. The uE miR-451a level was positively correlated with the change in eGFR and negatively correlated with serum creatinine, urinary macrophage migration inhibitory factor (MIF), interleukin-6 (IL-6) and tumor necrosis factor (TNF-α). A dual-luciferase reporter assay confirmed that MIF was a direct target of miR-451a. Receiver operating characteristic (ROC) curve analysis revealed that the expression of uE miR-451a showed potential diagnostic value for IgAN. Additionally, the uE miR-451a level could distinguish patients with IgAN with mild tubular atrophy/interstitial fibrosis from those with severe tubular atrophy/interstitial fibrosis. After a mean follow-up of 14.2 months, the levels of eGFR loss (ml/min/1.73 m2/year) were negatively correlated with baseline miR-451a. The levels of baseline miR-451a in the complete remission group were significantly higher than those in the non-complete remission group. uE miR-451a expression was significantly elevated in patients with IgA nephropathy and may serve as a potential biomarker for the diagnosis of IgAN and evaluation of tubulointerstitial damage, while the baseline levels of uE miR-451a may be predictors of therapeutic efficacy and disease progression.